Vibrational and thermodynamic properties of pure and gold adsorbed graphene. (August 2019) - Kaur, Gagandeep; Mann, Sarita; Gupta, Shuchi; Dharamvir, Keya
Abstract: We investigate the effect of adsorbed gold atom on phonon dispersion curves of a graphene sheet and calculate various thermodynamic properties of pure and gold-adsorbed graphene using Ab initio density functional perturbation theory (DFPT). The phonon frequencies have been calculated using Vienna ab initio Simulation Package (VASP) software in combination with phonopy code in the harmonic approximation. The variation of concentration of gold has been simulated by placing one and two gold atoms on graphene sheets containing successively 8 C-atoms (G8 ) and 32 C-atoms (G32 ). From phonon dispersion curves, it is clear that the change in the phonon frequencies of graphene with 3.125% Au adsorbent (G32 ) is negligible as compared to 12.5% of Au adsorbent (G8 ). An increase in the variation of entropy as well as specific heat with temperature is also observed upon Au adsorption in both graphene sheets as compared to pure graphene. But reverse trend is observed for the case of variation of free energy with temperature. Here, it decreases upon Au adsorption. Highlights: On comparing phonon DOS plots of Au@ G8 with that of pure G8, it is observed that all the van Hove's features are intact except that the peaks obtained are broadened and shifted towards lower frequencies. On adsorption of gold, DOS of both the sheets show an additional peak at very low frequency due to the vibration of the massive gold atom. This contributes a low T jump in specific heat. An increase in the variation of entropy as well as specific heat with temperature is also observed upon Au adsorption in both graphene sheets as compared to pure graphene. Reverse trend is observed for the case of variation of free energy with temperature. Here, it decreases upon Au adsorption. From the analysis of Cv versus T at low temperature, we find that only G8 curve has expected T 2 behavior whereas others do not have. However, overall behavior of Cv is as expected. Correspondingly changes are also observed in entropy and free energy curves at low temperature.